Strand 3: Gender Differences in an On-line Learning Environment: A Case Study - Lally, Vic; Barrett, Elizabeth (Proceedings of the International Conference on Networked Learning, 1998)
This paper focuses upon the use of Computer Mediated Communication (CMC) in a specific learning context by a small community of postgraduate (M.Ed.) distance learners and their tutors. Content analysis of on-line dialogues was used to investigate learning and socio-emotional behaviour within this community. The data presented suggests that men and women took distinctively different roles in our on-line learning environment. Most significantly, the cognitive and metacognitive (learning) content of on-line seminar contributions by men and women was found to be similar, but their social and interactive behaviour was significantly different. In particular, it was found that within a formal on-line learning environment men sent (on average) more messages than women; they wrote messages which were twice as long as those sent by women; and made more socio-emotional contributions than women. Women, however, were found to contribute more 'interactive' messages than men. This paper concludes that the application of CMC technology to a specific learning context may reproduce gender differences within a learning community.